Cloning and characterization of Sapp2p, the second aspartic proteinase isoenzyme from Candida parapsilosis - Merkerová, Michaela; Dostál, Jirí; Hradilek, Martin; Pichová, Iva; Hrusková-Heidingsfeldová, Olga (FEMS yeast research, 2006)
The human fungal pathogen Candida parapsilosis possesses at least three genes encoding secreted aspartic proteinases. Whereas the Sapp1p isoenzyme has already been biochemically characterized, the SAPP2 and SAPP3 gene products have not. The Sapp2p precursor, pro-Sapp2p, was therefore expressed in Escherichia coli and purified. Autoactivation of pro-Sapp2p in acidic conditions was inefficient and resulted in a protein extended by eight amino acids at the N-terminus (Sapp2p(+8)). The correct promature junction KR/SSPSS was cleaved by trypsin or by a membrane-bound Kex2-like proteinase from Candida parapsilosis. The mature Sapp2p obtained by the assisted activation was proteolytically active. Its activity was more than twofold higher than that of the self-processed protein species Sapp2p(+8), as measured by the hemoglobin cleavage test. The substrate specificity of Sapp2p differs from that of Sapp1p. Peptides containing aromatic residues in the P1 and P1' positions are cleaved poorly by Sapp2p. A fluorogenic substrate was synthesized to facilitate further studies.
Keywords: Molecular Sequence Data; klonování DNA; katalýza; Catalysis; aspartátové endopeptidasy; sekvence aminokyselin; Fungal Proteins; molekulární sekvence - údaje; Isoenzymes; Aspartic Acid Endopeptidases; fungální proteiny; Amino Acid Sequence; izoenzymy; Candida; Cloning, Molecular